Manipulation of Inorganic Atomic‐Layer Networks by Solution‐Phase Co‐assembly. Issue 54 (29th August 2017) - Hao, Yajiao; Yu, Lin; Dai, Chuying; Li, Song; Yu, Yang; Ju, Bo; Li, Minjie; Zhang, Sean Xiao‐An
Abstract: Homogeneous 2D lamellar assemblies of Au I thiolate coordination polymer (ATCP) were obtained by two‐ligand co‐assembly. The orbital levels and the bandgap of the 2D Au I –S network in the centre of the lamellae can be continuously tuned by means of the capping ligands on both sides, to give a new type of inorganic–organic composite semiconductor, the band structure of which can be easily tuned by low‐temperature solution‐phase co‐assembly. Furthermore, the chemical reactivity of these ATCP co‐assemblies also proved to be strongly dependent on the organic substituents, with well‐tuneable transformation rates to gold nanoparticles. Apparently, this is the first work to demonstrate how organic substituents can continuously tune the electron band structure and chemical reactivity of inorganic atomic layers of semiconductor through co‐assembly. Abstract : Two‐ligand co‐assembly : Homogeneous two‐dimensional nanosheets of Au I –thiolate coordination polymers were prepared by two‐ligand co‐assembly. The bandgap and orbital levels of the atomic layer of Au I –S network in the centre of the nanosheets were tuned by means of the organic substituents on both sides. The geometrical morphology and chemical reactivity of the co‐assemblies can also be adjusted through the content of co‐ligand (see figure).